جودة الخدمات بالمعايير الدولية فى المطارات دراسة تطبيقية على مطار مصرته الدولى - ليبيا - Abdulnaser Genah Mohamed Shaghdoun
The researcher has dealt with the quality of services in accordance with international standards for airports, taking Misurata International Airport, 2013 - 2014 AD, a model. The study has relied on two approaches: The inductive cognitive approach and the applied analytical descriptive approach . In order to measure the quality of services depending on a scale of five a dimensions, namely: reliability,responsiveness, tangibility, safety and compassion, the researcher distributed 300 questionnaires to random employees of Misurata International Airport as well as a range of customers (passsengers). After collecting 206 the questionnaire, the data was subjected to statistical analysis using SPSS program. The researcher interviewed the Assistant Manager of Misurata International Airport and the Director of Finance & Administration. The researcher has reached several conclusions, including: low-quality level of service, poor infrastructure, poor use of modern technology, lack of employee training, poor administrative system due to concentration of power, poor of task distribution, most of the workers and staff are not familiar with the laws of General Authority of Libyan Civil Aviation as well as lack of experienced air cargo companies. A comparison has been conducted between Hamad International Airport, and Misurata International Airport.The comparison shows that Misurata airport suffers a severe shortage in many aspects, and lacks basic components of air cargo. According to the study results, the researcher has presented recommendations aiming to improve the performance of Misurata International Airport. The recommendations include providing the airport with modern technology, staff training to keep pace with modern development, improvement of the airport infrastructure, increasing material incentives for workers, and spreading democratic atmosphere i.e. decisions must not be centralized superstructures.